Runx1 Orchestrates Sphingolipid Metabolism and Glucocorticoid Resistance in Lymphomagenesis. Issue 6 (10th January 2017) - Kilbey, A.; Terry, A.; Wotton, S.; Borland, G.; Zhang, Q.; Mackay, N.; McDonald, A.; Bell, M.; Wakelam, M.J.O.; Cameron, E.R.; Neil, J.C.
ABSTRACT: The three‐membered RUNX gene family includes RUNX1, a major mutational target in human leukemias, and displays hallmarks of both tumor suppressors and oncogenes. In mouse models, the Runx genes appear to act as conditional oncogenes, as ectopic expression is growth suppressive in normal cells but drives lymphoma development potently when combined with over‐expressed Myc or loss of p53. Clues to underlying mechanisms emerged previously from murine fibroblasts where ectopic expression of any of the Runx genes promotes survival through direct and indirect regulation of key enzymes in sphingolipid metabolism associated with a shift in the "sphingolipid rheostat" from ceramide to sphingosine‐1‐phosphate (S1P). Testing of this relationship in lymphoma cells was therefore a high priority. We find that ectopic expression of Runx1 in lymphoma cells consistently perturbs the sphingolipid rheostat, whereas an essential physiological role for Runx1 is revealed by reduced S1P levels in normal spleen after partial Cre‐mediated excision. Furthermore, we show that ectopic Runx1 expression confers increased resistance of lymphoma cells to glucocorticoid‐mediated apoptosis, and elucidate the mechanism of cross‐talk between glucocorticoid and sphingolipid metabolism through Sgpp1 . Dexamethasone potently induces expression of Sgpp1 in T‐lymphoma cells and drives cell death which is reduced by partial knockdown of Sgpp1 with shRNA or direct transcriptional repression of Sgpp1 by ectopic Runx1. Together these data show that Runx1 plays a role in regulating the sphingolipid rheostat in normal development and that perturbation of this cell fate regulator contributes to Runx‐driven lymphomagenesis. J. Cell. Biochem. 118: 1432–1441, 2017. © 2016 The Authors. Journal of Cellular Biochemistry Published by Wiley Periodicals, Inc. Abstract : Runx1 plays a role in regulating the sphingolipid rheostat in normal development. Perturbation of this cell fate regulator contributes to Runx driven lymphomagenesis by signaling resistance to glucocorticoid‐induced apoptosis and cell survival.